\(\frac{-12}{6}=\frac{x}{5}=\frac{-y}{3}=\frac{z}{-17}=\frac{-t}{-9}\)
=> \(\frac{x}{5}=-2\)
=>x = -10
=> \(\frac{-y}{3}=-2\)
=> -y = -6
=> y = 6
=> \(\frac{z}{-17}=-2\)
=> z = 34
=>\(\frac{-t}{-9}=\frac{t}{9}=2\)
=> t = 18
vậy x = -10 ; y = 6 ; z = 34 ; t = 18
duyệt nha các bn
Không biết làm thì đừng cmt điiiiiiiii
\(\frac{12}{-6}=\frac{x}{5}\Leftrightarrow x=\frac{12.5}{-6}=-10\)
\(\frac{12}{-6}=-\frac{y}{3}\Leftrightarrow y=6\)
\(\frac{12}{-6}=\frac{z}{-17}\Leftrightarrow z=34\)
\(\frac{12}{-6}=\frac{-t}{-9}\Leftrightarrow t=-18\)
Do 12/-6=x/5 nên 12.5/-6.x=>x =12.5/-6 => x=-10. Vậy x = -10
Do 12/-6=-y/3 nên 12.3=-6.-y=>-y=12.3/-6=>-y=-6=>y=6. Vậy y=6
Do 12/-6=z/-17 nên 12.-17=-6.z=>z=12.-17/-6=>z=34. Vậy z=34
Do 12/-6=-t/-9 nên 12. -9=-6. t=>t=12.-9/-6+>t=18. Vậy t=18
12/-6=-2
=> x/5=-2
=> x=-10
-y/3=-2
=> y=6
z/-17=-2
=> z=34
t/9=-2
=> t=-18